2017
DOI: 10.3389/fmicb.2017.00477
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Transcription Induced by Hydrogen Peroxide Treatment of Verotoxin-Producing Escherichia coli O157:H7 and Non-O157 Serotypes on Romaine Lettuce

Abstract: Disease outbreaks of verotoxin-producing Escherichia coli (VTEC) O157:H7 and non-O157 serotypes associated with leafy green vegetables are becoming a growing concern. A better understanding of the behavior of VTEC, particularly non-O157 serotypes, on lettuce under stress conditions is necessary for designing more effective control strategies. Hydrogen peroxide (H2O2) can be used as a sanitizer to reduce the microbial load in leafy green vegetables, particularly in fresh produce destined for the organic market.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 86 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…No significant differences in Sytox Green accessibility was detected between cells isolated from treated cultures and untreated cultures when stationary phase ETEC cultures incubated for 3 h at 37 • C in the presence or absence of up to 20 mM hydrogen peroxide, revealing intact membranes (Supplementary Figure 2). We note that this concentration of hydrogen peroxide is higher than typically used in reports of oxidative stress in laboratory (K12) strains of E. coli, and that higher concentrations (up to 50 mM) of hydrogen peroxide are usually necessary to induce stress in studies of pathogenic E. coli (Bearson et al, 2009;Felicio et al, 2009;Łoś et al, 2010;Mei et al, 2017). To validate that our treatment conditions nevertheless did result in oxidation of ETEC proteins, we analyzed whole cell extracts and observed an increase in oxidative carbonyl modifications (Supplementary Figure 3).…”
Section: Isolation and Proteomic Analysis Of Omvs Produced After Oxidative Stressmentioning
confidence: 84%
“…No significant differences in Sytox Green accessibility was detected between cells isolated from treated cultures and untreated cultures when stationary phase ETEC cultures incubated for 3 h at 37 • C in the presence or absence of up to 20 mM hydrogen peroxide, revealing intact membranes (Supplementary Figure 2). We note that this concentration of hydrogen peroxide is higher than typically used in reports of oxidative stress in laboratory (K12) strains of E. coli, and that higher concentrations (up to 50 mM) of hydrogen peroxide are usually necessary to induce stress in studies of pathogenic E. coli (Bearson et al, 2009;Felicio et al, 2009;Łoś et al, 2010;Mei et al, 2017). To validate that our treatment conditions nevertheless did result in oxidation of ETEC proteins, we analyzed whole cell extracts and observed an increase in oxidative carbonyl modifications (Supplementary Figure 3).…”
Section: Isolation and Proteomic Analysis Of Omvs Produced After Oxidative Stressmentioning
confidence: 84%
“…Past efforts showed that various stress conditions induced changes in E. coli gene expression in both pure culture and on non-host environments such as fresh lettuce (Allen and Griffiths, 2012;Mei et al, 2017). In this study, we analyzed the dynamic co-expression networks of E. coli in response to different doses of ClO 2 on non-host tomato surfaces, which could serve as a pre-exposure to another stressor causing either cross-protection or cross-vulnerability (Zorraquino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Average RPKM were transformed using the Propensity Transformation methodology that was optimized from the ClO 2 study on E . coli [ 66 ] based on the following equation: …”
Section: Methodsmentioning
confidence: 99%